Mithuna sculptures on mancha - Temples of India Project Team (Jio Institute, 2024)
Couples invoking shringara rasa (associated with romance, love, and attractiveness between lovers) are framed in panels with pillars and tiered shikhara with gavashka (horseshoe) motifs. The central figures are wearing heavy jewellery, elaborate headgear, and garments, indicating they are a royal couple. A central male figure is seated in a lalitasana pose on a raised seat, looking towards the central female figure seated on his left thigh, who is playing a stringed musical instrument. The female figure is also in a lalitasana pose and her right foot is resting on a footrest. Her body is slightly raised towards her left compared to the man. Hence, she is looking down towards the man. Positioned below her left leg is the figure of a male attendant. The central male figure is forcefully pulling a female attendant (holding a hand fan), towards him with his right hand. Behind the fan-holding female is a figure (face missing) wielding a sword.